CONGENITAL DENTOFACIAL ANOMALY. A HISTORY CASE OF SURGICAL TREATMENT OF TERATOID TUMOR ASSOCIATED WITH CONGENITAL CLEFT LIP AND PALATE IN A CHILD - O. V. Nelyubina; A. A. Mamedov; I. V. Kirgizov (Вопросы современной педиатрии)
The authors describe a history case of severe congenital dentofacial anomaly with congenital cleft lip, palate and alveolar ridge, associated with somatic disease. The diagnosis was confirmed histologically. The surgical treatment was performed after the careful presurgical preparation due to severe general condition of the child. The indication to the surgical treatment was a significant enlargement of the tumor mass since the child’s birth. The tumor filled the oral cavity and blocked oropharynx almost completely.